Evaluating the effectiveness of nurse enabled IEC package (Information, education and communication) on ill effects of alcohol, cannabis and nicotine use in terms of knowledge among students in selected colleges, Trichy - Mrs. X. Aron Christy,; Dr.Sivaraman M.D, (The Bioscan, 2025)
Background: Substance use among adolescents is increasing at an astounding rate globally posing a major threat to the health system and the society. This problem can be tackled if the adolescents are equipped with knowledge and positive attitude towards substance use. Materials and Methods: A evaluative study was conducted at selected colleges Trichy. Data was collected using self-structured questionnaire consisting of socio-demographic information and to assess the knowledge regarding substance use disorder. Analysis of the data was done using inferential and statistical methods. RESULTS: In post-test the majority had (78.6%) adequate knowledge. Table 3 shows that there was significant difference between pre-test and post-test knowledge (SD value 9.8) Table 4 shows that there is no significant association between the level of knowledge regarding the substance use disorder with their selected demographic variables. CONCLUSION: In post-test majority of the students had adequate knowledge and the IEC package was effective in improving the knowledge among college students.